Authentic User Light Intensity Control for Outdoor Application - Boddu, Rama Devi; Meeniga, Vijaya Lakshmi; Maddala, Vijaya Lakshmi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Outdoor lighting accounts for 75% of total demand and 19% of total energy consumption worldwide. The primary goal of this work is to control intensity of outdoor luminary system using Timer control, authentic user control (AUC) and hybrid control mode (HCM). The light intensity (LI) is regulated in different time zones based on the traffic on the road. In timer mode, the LI can be controlled based on the time zones. In AUC, the LI can be controlled by the authentic user by pressing a valid key from mobile. The AUC facilitates LI control (LIC) at midnight and on special occasions. In hybrid control mode, the LI of the luminaries can be controlled by timer and AUC. When authentic user presses the valid key, it overwrites the timer control, and based the key the LI is controlled. The luminaries operate in four different LIC modes. The LI may vary by 100%, 50%, 25%, and 0% (OFF). Three different modes are proposed in this work. They are: (i) auto-run self-test mode (ARSTM), (ii) normal mode (NM), and (iii) HCM. The luminaire working condition is tested using ARSTM. The NM has two operating modes: Timer mode (TM) and AUC mode (AUCM). In HCM, depending on the control inputs, the designed module operates based on timer and AUC inputs. The operation of the developed module is verified in ARSTM, NM, and HCM. Simple logic circuits are used in the proposed modules. This module used in rural, urban, other outdoor lighting applications and saves energy with LIC. It can be employed in outdoor LIC applications that rely on motion detection.